Wnt signaling is critical for maladaptive cardiac hypertrophy and accelerates myocardial remodeling - Malekar, Pratima; Hagenmüller, Marco; Anyanwu, Adamma; Buß, Sebastian Johannes; Streit, Marcus R.; Weiss, Celine; Wolf, David Gregor; Riffel, Johannes; Bauer, Alexander; Katus, Hugo; Hardt, Stefan (Hypertension, 2010)
The evolutionary conserved Wnt signaling pathway regulates cardiogenesis. However, members of the Wnt pathway are also expressed in the adult heart. Although Wnt-signaling is quiescent under normal conditions, we noticed activation on pathological stress of the heart, such as chronic afterload increase. To examine the role of Wnt signaling on the postnatal heart, we modified the expression and function of the Wnt regulator dishevelled 1 (Dvl-1) both in transgenic mice with cardiac-specific overexpression of Dvl-1 (Dvl-1-Tg) and in cultured cardiac myocytes. Dvl-1-Tg mice (3 months) had severe cardiac hypertrophy (heart weight:body weight ratio: 5.2±0.3 mg/g wild-type [WT] versus 6.4±0.7 mg/g Dvl-1-Tg; P<0.01), an increase in cardiomyocyte size (86% increase in Dvl-1-Tg compared with WT; P<0.01) and marked raise of atrial natriuretic factor expression (12-fold increase versus WT; P<0.01). Hypertrophy was associated with left ventricular dilatation in Dvl-1-Tg and a reduction of ejection fraction (4.4±0.1 mm versus 5.5±0.2 mm, 80±2% and 43±4% in WT versus Dvl-1-Tg, respectively; P<0.01). Transgenic animals died prematurely before 6 months of age. Both canonical as well as noncanonical Wnt signaling branches were activated in the Dvl-1-Tg animals. Small interfering RNA-mediated depletion of Dvl-1 was used to further characterize the role of Dvl-1 in cardiac myocytes. Whereas baseline parameters were unaltered, β-adrenergic hypertrophic response was abrogated in Dvl-1 knockdown cardiac myocytes, indicating a mandatory role in β-adrenergic stimulation. Therefore, activation of Wnt signaling is sufficient and critical for the induction of myocardial hypertrophy and cardiomyopathy.